Regresja hedoniczna i metoda conjoint measurement jako narzędzia w kształtowaniu polityki cenowej - Dziechciarz, Józef (Hedonic regression and conjoint measurement method as a tool for price policy improvement, 2005)
Both conjoint measurement technique and hedonic regression assumes that a product is a bunch of qualitative characteristics (attributes). Hedonic regression allows for price decomposition into prices of individual attributes. Conjoint measurement allows for estimation of partial utilities, which may interpreted as be attached (by consumer) towards individual variants (levels) of products’ attributes. By combining two mentioned techniques - new, unique possibility arises. It is possible to predict the results of the price policy. Solid base for prediction of the price policy is guaranteed by: Estimated values of partial utilities, which may interpreter as be attached (by consumer) towards individual variants (levels) of products’ attributes, indicate the hypothetic (predicted) weights attached in the future to the individual, qualitative attributes (precisely - the weights are attached to the levels of the attributes values). Estimates obtained from hedonic regression technique give the historic prices of the individual, qualitative attributes (precisely - the prices attached to the levels of the attributes values).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 42-55